Germline Mutations of BRCA1 and BRCA2 in Korean Ovarian Cancer Patients: Finding Founder Mutations. Issue 8 (October 2015) - Choi, Min Chul; Heo, Jin-Hyung; Jang, Ja-Hyun; Jung, Sang Geun; Park, Hyun; Joo, Won Duk; Lee, Chan; Lee, Je Ho; Lee, Jun Mo; Hwang, Yoon Young; Kim, Seung Jo
Abstract : Objectives: To investigate and analyze the BRCA mutations in Korean ovarian cancer patients with or without family history and to find founder mutations in this group. Methods/Materials: One hundred two patients who underwent a staging operation for pathologically proven epithelial cancer between January 2013 and December 2014 were enrolled. Thirty-two patients declined to analyze BRCA1/2 gene alterations after genetic counseling and pedigree analysis. Lymphocyte specimens from peripheral blood were assessed for BRCA1/2 by direct sequencing. Results: BRCA genetic test results of 70 patients were available. Eighteen BRCA1/2 mutations and 17 unclassified variations (UVs) were found. Five of the BRCA1/2 mutations and 4 of the UVs were not reported in the Breast Cancer Information Core database. One BRCA2 UV (8665_8667delGGA) was strongly suspicious to be a deleterious mutation. BRCA1/2 mutations were identified in 11 (61.1%) of 18 patients with a family history and in 7 (13.5%) of 52 patients without a family history. Candidates for founder mutations in Korean ovarian cancer patients were assessed among 39 BRCA1/2 mutations from the present study and from literature reviews. The analysis showed that 1041_1043delAGCinsT (n = 4; 10.2%) and 3746insA (n = 4; 10.2%) were possible BRCA1 founder mutations. Only one of the BRCA2 mutations (5804_5807delTTAA) was repeated twice (n = 2; 5.1%). Conclusions: The prevalence of BRCA1/2 mutations in Korean ovarian cancer patients irrespective of the family history was significantly higher than previously reported. Possible founder mutations in Korean ovarian cancer patients were identified.